2016
DOI: 10.1007/s11262-016-1367-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of Middle East respiratory syndrome coronavirus in dromedary camel farms linked with human infection in Abu Dhabi Emirate, United Arab Emirates

Abstract: The objective of this research was to investigate the prevalence of Middle East respiratory syndrome coronavirus (MERS-CoV) infection primarily in dromedary camel farms and the relationship of those infections with infections in humans in the Emirate of Abu Dhabi. Nasal swabs from 1113 dromedary camels (39 farms) and 34 sheep (1 farm) and sputum samples from 2 MERS-CoV-infected camel farm owners and 1 MERS-CoV-infected sheep farm owner were collected. Samples from camels and humans underwent real-time reverse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 28 publications
5
35
0
2
Order By: Relevance
“…These findings indicate that more attention should be given to assessing the risk of MERS-CoV infection in diabetic patients and whether the risk depends on a specific diabetes type or condition in these patients. As asserted in the Saudi MOH MERS-CoV visual triage guidelines and many other studies (Muhairi et al, 2016;Younan et al, 2016;Reeves et al, 2015;Sabir et al, 2016;Azhar et al, 2014a, b), contact with a sick patient or camel was identified as an independent predictor of MERS-CoV infection, according to the risk prediction model. It must be noted that the finding in the present study could have been limited by combining camel contact and sick patient contact due to the small sample size of each category.…”
Section: Discussionmentioning
confidence: 79%
“…These findings indicate that more attention should be given to assessing the risk of MERS-CoV infection in diabetic patients and whether the risk depends on a specific diabetes type or condition in these patients. As asserted in the Saudi MOH MERS-CoV visual triage guidelines and many other studies (Muhairi et al, 2016;Younan et al, 2016;Reeves et al, 2015;Sabir et al, 2016;Azhar et al, 2014a, b), contact with a sick patient or camel was identified as an independent predictor of MERS-CoV infection, according to the risk prediction model. It must be noted that the finding in the present study could have been limited by combining camel contact and sick patient contact due to the small sample size of each category.…”
Section: Discussionmentioning
confidence: 79%
“…Our search found that dromedary populations in 16 countries have been tested for MERS-CoV RNA, 13 of which report positive results indicating active infection. These include KSA (0.12-56%) (Alagaili et al, 2014;Khalafalla et al, 2015;Sabir et al, 2016;Alfuwaires et al, 2017;Kasem et al, 2018a, b), UAE (0-29% (Wernery et al, 2015a, b;Yusof et al, 2015;Li et al, 2017;Yusof et al, 2017) or 0-100% if dromedaries epidemiologically linked to human MERS-CoV cases are included(Al Hammadi et al, 2015;Muhairi et al, 2016;Paden et al, 2018)), Qatar (22-79%) Reusken et al, 2014a;Farag et al, 2015;Mohran et al, 2016), Oman (7%) (Nowotny and Kolodziejek, 2014), Iraq (15%) (Al Salihi and Alrodhan, 2017), and Jordan (62%) (van Doremalen et al, 2017), as well as Egypt (4-15%) , Ali et al, 2017a, Ethiopia (10%) (Miguel et al, 2017), Kenya (0.35-0.95%) (Kiambi et al, 2018;Ommeh et al, 2018), Nigeria (3-11%) So et al, 2018), Burkina Faso (5%) (Miguel et al, 2017), Morocco (2%) (Miguel et al, 2017), and Pakistan (3%) . See Fig.…”
Section: Prevalence Of Active Mers-cov Infection -Cross-sectional Stumentioning
confidence: 99%
“…We found 10 longitudinal studies describing 9 incidences of natural infection on farms and in quarantine facilities -1 in Egypt (Ali et al, 2017b), 4 in KSA (Azhar et al, 2014;Hemida et al, 2014a;Memish et al, 2014;Hemida et al, 2017a), 5 in UAE (Al Hammadi et al, 2015;Wernery et al, 2015a;Meyer et al, 2016;Muhairi et al, 2016;Yusof et al, 2017) and 1 study taking monthly samples of 430 dromedaries in Kenya (Kiambi et al, 2018).…”
Section: Evidence Of Infection and Immunity From Longitudinal Studiesmentioning
confidence: 99%
“…Experimental challenge and transmission studies provided key data regarding the time course of infection. Field studies have also provided valuable information, including evidence supporting the duration of pathogen shedding (Al Muhairi et al, ), and documenting transmission among dromedaries (Ali, Shehata, et al, ; Meyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the upper respiratory tract is now understood to be the primary site of viral replication and shedding, it is important to understand the role of other potential routes of transmission for understanding risk. Therefore, the negative results of observational studies (Al‐Muhairi et al, ; Azhar et al, ) are as important as the positive findings (Ali, El‐Shesheny, et al, ; Reusken et al, ) as they provide a more complete picture of possible routes of transmission.…”
Section: Discussionmentioning
confidence: 99%